ISOLATION AND SCREENING OF ANTIMICROBIAL COMPOUNDS OF MICROMONOSPORA STRAINS ISOLATED FROM HA LONG – CAT BA BAY’S SEDIMENTS - Minh, Lê Thị Hồng; Quyên, Vũ Thị; Anh, Nguyễn Mai; Cường, Phạm Việt; Cường, Phạm Văn; Mai Hương, Đoàn Thị; Murphy, Brian T.; Minh, Châu Văn (Vietnam Journal of Science and Technology, 2016)
Microorganisms are especially interested due to the ability to produce secondary compounds with high value application. The bioactive substances could give us new and varied chemical structures. In this study, 39 strains of actinomycetes were isolated from 9 Sediments samples. The strains were fermented in A1 medium, fermentation broths were extracted 5 times with ethyl acetate, then the residue of extracts was collected to test the activity against some reference bacteria. From the results of screening, 3 strains of actinomycetes that have the highest biological activity (Code: G016, G017, G019) were selected. These strains have the quite strong inhibition on two strains of Gram positive bacteria: as Enterococcus faecalis ATCC29212 and Bacillus cereus ATCC13245 with MIC values less than or equal to the MIC value of the reference antibiotic (MICG016 = 64 µg/ml, MICG017 =  128 µg/ml, MICG019 = 64 µg/ml). In addition, two strains G017 and G019 were active against Candida albicans ATCC10231 with respective values  MICG017 = 2 µg/ml, MICG019 = 8 µg/ml. These strains were subjected to morphological and phylogenetic investigation based on 16S rRNA gene sequences. The obtained results indicate that strains G016, G017, and G019 belong to Genus Micromonospora.